Development of work Standardization and Measurement of Employee Satisfaction to Support Business Management in Beverly Florist MSMEs - Ananda, Inelia Putri; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2023)
In running its business, an SME needs to pay attention to several management aspects, one of which is human resource management. The aim of this activity is to develop work standardization and measure employee satisfaction to support business management at Beverly Florist. The method used is providing knowledge in the form of employee job desks, preparing effective picket schedules, and measuring employee job satisfaction. The results of these activities show that the development of human resource standardization at Beverly Florist has increased as indicated by more structured operational effectiveness.